The influence of temperature on the solubility limit of Ca in alumina. Issue 15 (December 2020) - Ghosh, Priyadarshini; Marder, Rachel; Berner, Alex; Kaplan, Wayne D.
Graphical abstract: Abstract: Dopants and impurities can adsorb to surfaces and grain boundaries in ceramics, influencing the sintering kinetics and grain boundary mobility during processing. Ca is a common impurity in alumina that promotes grain growth at concentrations below the solubility limit, in contrast to the commonly observed solute-drag effect. Knowledge of the Ca solubility limit at temperatures relevant to processing is important to control microstructural evolution. Here we report on the experimentally measured solubility limit of Ca in α-alumina at 1400 °C and 1500 °C from equilibrated and quenched samples using standardized wavelength dispersive spectroscopy to be 32 ± 3 ppm and 45 ± 3 ppm, respectively. Together with the previously measured Ca solubility limit at 1600 °C, the enthalpy (0.95 eV per Ca) and vibrational entropy (-7.35 × 10 −4 eV K -1 per Ca) of solution were determined. A negative vibrational entropy of solution indicates coulombic interactions between the Ca cations and charge compensating defects in α-alumina.